Developing EFL Critical Reading Aids: Project-Based Learning Activities for Electrical Industrial Engineering Students - Khulaifiyah, Khulaifiyah; Milawati, Milawati; Suparti, Suparti (UIR Press, 2024)
The Independent Learning and Independent Campus (MBKM) curriculum for vocational education provided learning experiences for students. However, the reading material conducted had not reached the curriculum target. Thus, this study aimed to develop critical reading material and worksheets based on the MBKM curriculum. The development procedure was designed in three stages: defining, designing, and developing for 3-D aids. The research resources employed were validation sheets for critical reading aids and semi-observation sheets to provide student activity during PjBL field trial. The results of this study were project-based learning (PjBL) used to construct English language learning aids for the syllabus and coursework units, including worksheets for critical reading. Hence, this learning aid could slightly enhance students' reading competence, which could lead them to have soft and hard skills as well as meet the MBKM curriculum target.